WORKING CAPITAL MANAGEMENT MODEL IN WOMEN'S COOPERATIVES - Achmad Murdiono; Imam Mukhlis; Arief Noviarakhman Zagladi (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2023)
The presence of Women's Cooperatives or also known as "Kopwan" in society is crucial for aiding the government in addressing economic challenges, reducing unemployment, enhancing family financial well-being, and tackling gender issues. Despite their significant role, the existence of Kopwan requires careful attention, as many face stagnation at the business level, attributed in part to challenges in effectively managing working capital. This qualitative descriptive research aims to elucidate the meaning, sources, and management of working capital for Kopwan, utilizing data gathered through interviews and observational methods. The qualitative descriptive approach is chosen for its ability to directly depict and interpret the phenomena occurring in the investigated field. The findings reveal that Kopwan views working capital not merely as money but also as trust and networks. The management of working capital in Kopwan encompasses planning, organizing, and monitoring stages, and the applied model has proven effective in helping cooperatives successfully navigate operational aspects and enhance financial performance.